Poor oral health including active caries in 187 UK professional male football players: clinical dental examination performed by dentists. Issue 1 (2nd November 2015) - Needleman, Ian; Ashley, Paul; Meehan, Lyndon; Petrie, Aviva; Weiler, Richard; McNally, Steve; Ayer, Chris; Hanna, Rob; Hunt, Ian; Kell, Steven; Ridgewell, Paul; Taylor, Russell
Abstract : Background: The few studies that have assessed oral health in professional/elite football suggest poor oral health with minimal data on impact on performance. The aim of this research was to determine oral health in a representative sample of professional footballers in the UK and investigate possible determinants of oral health and self-reported impact on well-being, training and performance. Methods: Clinical oral health examination of senior squad players using standard methods and outcomes carried out at club training facilities. Questionnaire data were also collected. 8 teams were included, 5 Premier League, 2 Championship and 1 League One. Results: 6 dentists examined 187 players who represented >90% of each senior squad. Oral health was poor: 37% players had active dental caries, 53% dental erosion and 5% moderate-severe irreversible periodontal disease. 45% were bothered by their oral health, 20% reported an impact on their quality of life and 7% on training or performance. Despite attendance for dental check-ups, oral health deteriorated with age. Conclusions: This is the first large, representative sample study in professional football. Oral health of professional footballers is poor, and this impacts on well-being and performance. Successful strategies to promote oral health within professional football are urgently needed, and research should investigate models based on best evidence for behaviour change and implementation science. Furthermore, this study provides strong evidence to support oral health screening within professional football.